Optimizing the Training Model for Field Engineers to Meet Industrial Development Needs: A Case Study of Vocational Education - Rui Huang (International Journal of Education and Humanities, 2025)
With the rapid implementation of Shenzhen's "20+8" industrial cluster strategy, the demand for technical skills in emerging industries has surged. There is an urgent need for field engineers equipped with practical operational expertise, process understanding, managerial competencies, and innovative thinking. However, the current vocational education landscape faces opportunities and challenges in meeting the needs of industrial upgrading. Addressing how to construct and optimize the training model for field engineers has become a critical issue. This study aims to propose strategies and pathways for developing field engineers aligned with Shenzhen’s industrial development needs. Using methods such as literature review and case analysis, this research examines the innovative practices of Shenzhen Polytechnic University. Key focus areas include curriculum system design, teacher team development, industry-education integration, and evaluation system reforms. The findings highlight these practices' positive effects on enhancing vocational education quality and supporting industrial upgrading. Based on these insights, the study concludes with recommendations for refining the training model for field engineers in future vocational education. These include fostering deeper collaboration between industry and education, emphasizing innovation in curriculum design, and adopting comprehensive evaluation mechanisms to ensure alignment with evolving industrial demands. This research provides a valuable framework for addressing the challenges of vocational education in an era of rapid industrial transformation